A Cytogenetic Study of Three Japanese Cultivars of Momordica charantia L. - Michiko Kido; Atsumi Morikawa; Kanjana Saetiew; Yoshikazu Hoshi (My University, 2016)
Using a base-specific staining method, three Japanese cultivars of Momordica charantia were investigated. The present method using enzymatic digestion produced a high level of well-spread metaphase chromosome complements. The cultivars investigated showed the same somatic chromosome number 2n=22. In condensation behavior from prophase to metaphase, most chromosomes of all cultivars in this study had early condensing segments at the proximal regions. Moreover, at prophase or earlier stage of metaphase, most chromosomes observed had decondenced segments at the distal regions in both arms. Judging by the determination of centromere positions, the chromosome complements at mitotic metaphases in three cultivars consisted of 22 metacentric chromosomes. Moreover, similar sizes and shapes of the chromosomes indicated that the karyotypes of M. charantia cultivars were symmetrical. In contrast, fluorescent staining showed different sizes and numbers of chromycin A3 (CMA) positive and 4′,6-diamidino-2-phenylindole (DAPI) negative (CMA+DAPI−) satellites among cultivars. Four CMA+DAPI− satellites were observed in M. charantia ‘Abashi-goya’ and M. charantia ‘Naga-goya,’ while two satellites were obseved in M. charantia ‘Shiro-goya.’ All satellites were located at one end of sat-chromosomes. In ‘Shiro-goya,’ a large size difference of satellites was found between two sat-chromosomes, which might be homologous chromosomes with polymorphism. Moreover, faintly CMA+DAPI− sites were shown at the proximal regions or primary constrictions of most chromosomes in all cultivars.
Keywords: DAPI; Chromosomal and Genetic Variations